PENGEMBANGAN PERANGKAT PEMBELAJARAN STEAM PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN ARGUMENTASI MATEMATIS SISWA - Emas Marlina; Dini Andiani (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to develop a valid, practical, and effective STEAM Project-Based Learning (PjBL) instructional device to improve junior high school students’ critical thinking and mathematical argumentation skills. The study employed a Research and Development (R&D) method using the Dick and Carey instructional design model, which consists of nine systematic stages. The participants were eighth-grade students in Bandung Regency. The instruments included expert validation sheets to assess validity, teacher and student response questionnaires to evaluate practicality, and pre-test and post-test instruments to measure effectiveness. The product was validated by two experts in media and subject matter. Practicality was determined based on teacher and student responses, while effectiveness was measured using the N-gain score. The results indicated that the developed instructional device was highly valid and feasible for implementation. The material expert validation achieved an average score of 96.48%, and the media expert validation reached 95.25%, both categorized as very high. The practicality test showed very positive responses, with teacher responses averaging 95% and student responses 93%. Furthermore, the effectiveness test demonstrated high N-gain scores of 0.75 for mathematical critical thinking and 0.77 for mathematical argumentation skills, indicating significant improvement in both competencies.